2013
DOI: 10.1177/0081175012470644
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Association between Latent Class Membership and External Variables Using Bias-adjusted Three-step Approaches

Abstract: Latent class analysis is a clustering method that is nowadays widely used in social science research. Researchers applying latent class analysis will typically not only construct a typology based on a set of observed variables but also investigate how the encountered clusters are related to other, external variables. Although it is possible to incorporate such external variables into the latent class model itself, researchers usually prefer using a three-step approach. This is the approach wherein after establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
429
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 462 publications
(477 citation statements)
references
References 29 publications
13
429
1
Order By: Relevance
“…Asparouhov & Muthén, 2014a;Vermunt, 2010) or a predictor of an outcome (e.g. Bakk, Tekle, & Vermunt, 2013;. Of these two extensions, the latter is of particular interest in life-course research where questions of interest include how childhood circumstances influence later life outcomes such as overall well-being.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Asparouhov & Muthén, 2014a;Vermunt, 2010) or a predictor of an outcome (e.g. Bakk, Tekle, & Vermunt, 2013;. Of these two extensions, the latter is of particular interest in life-course research where questions of interest include how childhood circumstances influence later life outcomes such as overall well-being.…”
Section: Introductionmentioning
confidence: 99%
“…There are three main advantages of the 1-step approach. First, it is more efficient compared to step-wise approaches that may introduce additional uncertainty between steps; second it allows for more flexible model structures, such as models with direct effects of covariates on indicators and the distal outcome; and, third, it is straightforward to account for residual correlation between Z and U s, beyond that captured by class membership (Bakk et al, 2013). However, the 1-step approach has received criticism over the past ten years regarding the practicality of the simultaneous estimation and the requirement for additional distributional assumptions about Z.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Bachl and Scharkow (2017), we used a more elaborated least squares procedure with equality and inequality constraints (lsei() from the limSolve package; Soetaert, Van den Meersche, & van Oevelen, 2009) to guarantee corrected proportions inside the range between 0 and 1. Similar correction procedures are implemented in Mplus (Asparouhov & Muthén, 2014) and Latent Gold (Bakk, Tekle, & Vermunt, 2013), where they are used in the context of latent class analysis. They could also be adapted to correct the estimated proportions from the content analysis part of a linkage study given the observed data and an approximation of the misclassification probabilities.…”
Section: Possible Remedies Ii: Correcting For the Consequences Of Meamentioning
confidence: 99%